What we need to flourish: rethinking external goods and the ecological systems that provide them - Shockley, Kenneth, speaker; Didier, John, speaker; Rolston, Holmes, 1932-2025, speaker; Frank, Tony, speaker; Miranda, Rick, speaker (Colorado State University. Libraries, 2016)
Kenneth Shockley gives his Inaugural Lecture in Holmes Rolston III Endowed Chair in Environmental Ethics and Philosophy, October 14, 2016. How should we balance the need for development with the need for environmental protection? Too often development and environmental protection are thought of as being at odds. Shockley argues that just as development requires we support robust social systems, so it requires we support robust ecological systems. Rather than being at odds with one another, development requires robust environmental protection.
Includes appearances by John Didier, Philosophy Chair; Holmes Rolston III; CSU President Dr. Tony Frank; Rick Miranda, Provost.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: environmental ethics; nature; natural resources; social goods; natural goods; external goods; environmental goods; constitutive dependence; constitutive value; intrinsic value; systemic value; human development; Sen, Amartya; environmental blind spot; ecosystems and human well being; Rolston, Holmes, 1932-2025